2016
DOI: 10.6061/clinics/2016(05)01
|View full text |Cite
|
Sign up to set email alerts
|

The urine albumin-to-creatinine ratio is a reliable indicator for evaluating complications of chronic kidney disease and progression in IgA nephropathy in China

Abstract: OBJECTIVE:This study investigated the correlation between the albumin-to-creatinine ratio in the urine and 24-hour urine proteinuria and whether the ratio can predict chronic kidney disease progression even more reliably than 24-hour proteinuria can, particularly in primary IgA nephropathy.METHODS:A total of 182 patients with primary IgA nephropathy were evaluated. Their mean urine albumin-to-creatinine ratio and 24-hour proteinuria were determined during hospitalization. Blood samples were also analyzed. Foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 35 publications
2
7
0
2
Order By: Relevance
“…27 In addition, creatinine level in saliva can also be used to diagnose CKD. Ratio of albumin-to-creatinine in urine was reported as a reliable predicator of CKD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…27 In addition, creatinine level in saliva can also be used to diagnose CKD. Ratio of albumin-to-creatinine in urine was reported as a reliable predicator of CKD.…”
Section: Discussionmentioning
confidence: 99%
“…Ratio of albumin-to-creatinine in urine was reported as a reliable predicator of CKD. 27 In addition, creatinine level in saliva can also be used to diagnose CKD. 28 Moreover, Silva et al 29 reported that creatinine in dry blood sample is a convenient marker for CKD screening.…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies showed this correlation in patients with CKD or normal kidney function [6, 11, 21, 22]. However, only a few studies focused on IgAN to investigate the association [23, 24]. Among patients with glomerulonephritis in this cross-sectional study, high correlation coefficients (r = 0.91, 95% CI: 0.95–0.98) were observed [23].…”
Section: Discussionmentioning
confidence: 49%
“…Among patients with glomerulonephritis in this cross-sectional study, high correlation coefficients (r = 0.91, 95% CI: 0.95–0.98) were observed [23]. In addition, in a cohort study of 182 selected patients with primary IgAN, a good correlation was found between urine albumin-to-creatinine ratio and 24HP, except those pertaining to CKD stage 5, in patients with IgAN [24]. In the current study, similar results were observed.…”
Section: Discussionmentioning
confidence: 88%
“…Microalbuminuria has been shown to co-present with hematuria more often in those with IgAN; however, its sensitivity and specificity are too low to be of any value in clinical practice ( 96 ). Furthermore, the albumin-to-creatine ratio (ACR) yields little benefit over UPCR in IgAN ( 97 , 98 ).…”
Section: Traditional Biomarkers Currently Used In the Management Of Imentioning
confidence: 99%